Management of Presbyphonia - Fauziah Fardizza; Mirta Hediyati Reksodiputro (PERHATI-KL, 2020)
Background: The proportion of individuals over 65 years of age in developed countries is increasing rapidly, due in large part to current and projected increases in life expectancy.Within the aging population, the incidence of vocal disorders is estimated to be between 12%-35%. Literature Review: Presbyphonia, or age-related dysphonia, is a diagnosis of exclusion. Patients’ other comorbidities must be evaluated completely. The complexity of presbyphonia involves the changes in the diverse tissues of the true vocal folds, musculature, and cartilage. Patients would get benefit from treatment of voice therapy or surgical laryngeal augmentation procedures. Purpose: The aim of this literature review is to describe presbyphonia and several kinds of its management. The primary treatment goal is to enhance glottal closure either by voice therapy or surgical interventions (phonosurgery) such as injection augmentation (IA) and bilateral thyroplasty surgery (BTS). Holistic physical evaluation had to be done to reach complete medical therapy. Conclusion: The best therapy for presbyphonia are voice therapy, or surgery followed by voice therapy and voice hygiene.Keywords: vocal disorder, presbyphonia, voice therapy, phonosurgery, management ABSTRAKLatar belakang: Prevalensi individu yang berusia diatas 65 tahun di negara maju semakin meningkat dengan cepat seiring dengan meningkatnya usia harapan hidup. Dalam populasi lanjut usia, angka kejadian gangguan fonasi diperkirakan antara 12%-35%. Tinjauan Pustaka: Presbifonia, atau disfonia terkait usia lanjut, membutuhkan evaluasi faktor komorbid secara lengkap. Kerumitan dari presbifonia adalah karena melibatkan perubahan jaringan, otot, dan tulang rawan di sekitar pita suara. Tatalaksana yang dilakukan adalah perawatan terapi suara dan prosedur bedah augmentasi pita suara. Tujuan: Untuk menggambarkan presbifonia serta berbagai jenis tatalaksananya. Keberhasilan utama penatalaksanaan presbifonia adalah meningkatnya penutupan glotis, baik dengan terapi suara atau intervensi bedah (phonosurgery) seperti injeksi augmentasi dan bedah tiroplasti bilateral. Dibutuhkan evaluasi fisik secara holistik untuk mencapai hasil terapi medis yang baik. Kesimpulan: Penatalaksanaan terbaik untuk presbifonia adalah terapi suara, atau pembedahan diikuti dengan terapi suara dan higiene suara.